Pediatric audiology casebook (New York : Thieme, 2011)
"Pediatric Audiology Casebook bridges the gap between content knowledge and clinical application in an accessible manner that will enable readers to put learned theory into active practice by engaging them in problem-based learning. This compendium of key cases is an excellent choice for the classroom, covering everything from basic and complex diagnostic cases, to hearing aid technology, vestibular issues, and the management of auditory development. Each case is consistently organized, beginning with the patient's clinical history and audiologic testing. The authors then pose a series of evaluative questions to the reader, followed by carefully considered, thought-provoking answers designed to foster understanding. Cases close with a discussion of the definitive diagnosis, recommended treatment options, and the final outcome"--Provided by publisher.
Includes bibliographical references.
Keywords: Hearing disorders in children -- Case studies; Hearing disorders in children -- Diagnosis; Hearing disorders in children -- Treatment; Hearing Loss -- Case Reports. -- diagnosis